2012
DOI: 10.3400/avd.oa.12.00010
|View full text |Cite
|
Sign up to set email alerts
|

Early Outcomes of Open Abdominal Repair Versus Endovascular Repair for Abdominal Aortic Aneurysm: Report from National Hospital Organization Network Study in Japan

Abstract: Objective: Early outcomes of open abdominal repair (OS) versus endovascular repair (EVAR) forabdominal aortic aneurysm were retrospectively analyzed, after commercialized devices for EVAR had become available in Japan. Patients and Methods: A total of 781 consecutive patients (OS, n = 522; EVAR, n = 259) were treated at ten medical centers between January 2008 and September 2010. The OS group comprised patients with preoperative shock (SOS, n = 34) and without shock (NOS, n = 488). Results: Patients in the EVA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…8,9) Rates of EVAR for AAA have been increasing yearly because of the lower degree of invasiveness, with rates reaching 53% in 2011. 8,9) Rates are likely to have increased since 2011, making EVAR the main surgical method for AAA. The major differences between EVAR and OS include the risk of residual endoleak, radiation exposure, and use of contrast medium.…”
Section: Discussionmentioning
confidence: 99%
“…8,9) Rates of EVAR for AAA have been increasing yearly because of the lower degree of invasiveness, with rates reaching 53% in 2011. 8,9) Rates are likely to have increased since 2011, making EVAR the main surgical method for AAA. The major differences between EVAR and OS include the risk of residual endoleak, radiation exposure, and use of contrast medium.…”
Section: Discussionmentioning
confidence: 99%
“… 4 9 ) Because EVAR has several contraindications in such patients, including a short neck or a narrow access route, 10 ) whether conventional open repair should be performed remains controversial due to the increased mortality and morbidity associated with patient age. 11 , 12 ) Moreover, a small number of reports have concluded that EVAR is also suitable for nonagenarians, 4 , 5 , 8 , 9 ) although the outcomes of open repair in nonagenarians remain unclear. In the present study, the outcomes of conventional open repair for AAA were compared with those of EVAR in nonagenarian patients.…”
Section: Introductionmentioning
confidence: 99%
“…10,11) In brief, indications for treating infra-renal AAA in the present study were as follows: a maximum diameter greater than or equal to 5 cm or 4-5 cm with rapid enlargement of 5 mm or more over 6 months or a saccular morphology that carried a high risk of rupture. Each patient had a preoperative examination, including a multi-detector computed tomography (CT) examination according to the requirements in each participating center.…”
Section: Patients and Registrationmentioning
confidence: 99%